Diversity of Medical Plant Resources on Mam Du Island, Kien Giang Province - Minh Quan, Dang; Minh Khoa, Tran; Thanh Phuc, Nguyen; Minh Phuong, Truong (VNU Journal of Science: Natural Sciences and Technology, 2018)
Abstract: This study was conducted on Nam Du Island (Kien Hai district, Kien Giang province) from October 2017 to September 2018 to assess the diversity of the local medicinal plant resources. Through the study of the collected samples of the local medicinal plants, 443 medicinal plants belonging to 316 genera, 128 families of four divisions were identified. Of the four divisions, the Magnoliophyta was the most diverse with 88.28% of the families, 94.30% of the genera and 94.81% of the species. Nine of the identified species are listed in “Medicinal plants in Vietnam’s Red List” (2006), “Vietnam Red Book” (2007) and the Prime Minister’s Decree 32/CP/2006. The identified medicinal plant species were divided into twelve life forms and six biotopes, with the highest species diversity in the mountainous natural forest biotope (55.76%) and garden biotope (51.47%). Ten different parts of the identified plants are used as herbal medicine in the treatment of 36 diseases and twenty-seven medicinal plant species are commonly used by the local people. Keywords: Biotope, diversity, medical plant, Nam Du Island of Kien Giang province. References [1] Nguyễn Duy Cần và Nico Vromant, PRA - Đánh giá nông thôn với sự tham gia của người dân, Nxb Nông nghiệp, Thành phố Hồ Chí Minh, 2009. [2] Nguyễn Nghĩa Thìn, Các phương pháp nghiên cứu thực vật, NxbĐại học Quốc gia Hà Nội, Hà Nội, 2007. [3] Sở Tài nguyên & Môi trường tỉnh Kiên Giang, Báo cáo quy hoạch sử dụng đất đến năm 2015 và định hướng đến năm 2020, Kiên Giang, 2014. [4] Phạm Hoàng Hộ, Cây cỏ Việt Nam (3 quyển), Nxb Trẻ, Thành phố Hồ Chí Minh, 1999 – 2000. [5] Võ Văn Chi, Từ điển thực vật thông dụng (2 tập), Nxb Khoa học và Kỹ thuật, Hà Nội, 2002, 2004. [6] Trung tâm Nghiên cứu Tài nguyên và Môi trường - Đại học Quốc gia Hà Nội, Danh lục các loài thực vật Việt Nam, tập I, Nxb Nông nghiệp, Hà Nội, 2001. [7] Trung tâm Nghiên cứu Tài nguyên và Môi trường - Đại học Quốc gia Hà Nội, Viện Sinh thái và Tài nguyên sinh vật, Danh lục các loài thực vật Việt Nam, tập II, III, Nxb Nông nghiệp, Hà Nội, 2003, 2005. [8] Võ Văn Chi, Từ điển cây thuốc Việt Nam, tập 1, 2, Nxb Y học, Hà Nội, 2012. [9] Đỗ Tất Lợi, Những cây thuốc và vị thuốc Việt Nam (Có sửa chữa và bổ sung), Nxb Y học và Nxb Thời đại, Hà Nội, 2015. [10] Bộ Nông nghiệp và Phát triển Nông thôn, Vụ Khoa học Công nghệ và Chất lượng sản phẩm, Tên cây rừng Việt Nam, Nxb Nông nghiệp, Hà Nội, 2000. [11] Nguyễn Tập, Danh lục đỏ cây thuốc Việt Nam năm 2006, Tạp chí Dược liệu,số 3(11), trang 97-105, 2006. [12] Bộ Khoa học và Công nghệ, Viện Khoa học và Công nghệ Việt Nam, Sách đỏ Việt Nam – Phần II: Thực vật, Nxb Khoa học Tự nhiên và Công nghệ, Hà Nội, 2007. [13] Chính phủ nước Cộng hòa xã hội chủ nghĩa Việt Nam, Nghị định 32/2006/NĐ-CP, ngày 30/03/2006 của Chính phủ về Danh mục thực vật rừng, động vật rừng nguy cấp, quý, hiếm, Hà Nội, 2006. [14] Bộ Y Tế, Thông tư số 40/2013/TT - BYT về Ban hành danh mục thuốc thiết yếu thuốc đông y và thuốc từ dược liệu lần VI, Hà Nội, 2013.